PWE-033 Promoter Region Variations in The Glutaminase Gene as A Risk Factor for The Development Hepatic Encephalopathy in Patients with Cirrhosis. (17th August 2016) - Goh, ET; Way, MJ; Atkinson, SR; McQuillin, A; Morgan, MY
Abstract : Introduction: Hepatic encephalopathy (HE) is the commonest complication of cirrhosis but its development is not invariable; thus approximately 20% of individuals remain free of neuropsychiatric complications and patients with minimal HE do not invariably develop overt HE. It is possible that genetic factors, most likely resulting in deregulation of ammonia metabolism, might determine an individual's susceptibility to develop this complication. In 2010, Romero-Gomez and colleagues, 1 identified a functional microsatellite consisting of GCA repeats near the promoter region of the glutaminase gene, GLS1, and proposed that patients with cirrhosis who were homozygous for the long microsatellite allele were more likely to develop overt HE. The aim of this study was to further investigate the association between GLS1 promoter microsatellite variants and HE. Methods: The study population comprised 110 patients with cirrhosis, of British/Irish ancestry, in whom neuropsychiatic status had remained stable during monitoring for a minimum of 5 years, except in those treated for overt HE. Patients were classified using clinical, neurophysiological and neuropsychometric variables as: unimpaired (51; 46%) or as having minimal (24; 22%) or overt (35; 32%) HE. The control population comprised 325 ancestrally-matched healthy controls. DNA was genotyped using gel electrophoresis and verified by Sanger sequencing. Alleles were stratified as long (≥14 GCA repeats) or short (<14 GCA repeats). Genotype distributions and allele frequencies were compared between groups. Results: There were no significant differences in allele frequencies or genotype distributions between cases and controls. The proportion of long-short heterozygotes was significantly higher in the unimpaired patients (62.7%) than in those with either minimal HE (37.5%) or overt HE (37.1%) (p = 0.029; Table ). Conclusion: There was no evidence that the long-long genotype is a risk factor for HE in the present study. However, there was evidence of possible heterozygote advantage resulting in significant protection against the development of this syndrome. More studies are needed to confirm or refute these findings. Reference: 1 Romero-Gomez M, et al . Variations in the promoter region of the glutaminase gene and the development of hepatic encephalopathy in patients with cirrhosis: a cohort study. Ann Intern Med 2010;153 :281–8. Disclosure of Interest: None Declared